2000
DOI: 10.1090/s0002-9939-00-05587-8
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Kähler and the symplectic structures from certain spinors on 4-manifolds

Abstract: Abstract. We show that, on an oriented Riemannian 4-manifold, existence of a non-zero parallel spinor with respect to a spin c structure implies that the underlying smooth manifold admits a Kähler structure. A similar but weaker condition is obtained for the 4-manifold to admit a symplectic structure. We also show that the spin c structure in which the non-zero parallel spinor lives is equivalent to the canonical spin c structure associated to the Kähler structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Remark 3.10. This last result was obtained independently in [BLPR01]. Note also that this is only the spin C version of a similar statement holding for genuine spinstructures: If M admits a spin-structure with a parallel spinor field, then M is Kähler.…”
Section: Splitting the Connectionmentioning
confidence: 58%
See 1 more Smart Citation
“…Remark 3.10. This last result was obtained independently in [BLPR01]. Note also that this is only the spin C version of a similar statement holding for genuine spinstructures: If M admits a spin-structure with a parallel spinor field, then M is Kähler.…”
Section: Splitting the Connectionmentioning
confidence: 58%
“…While this work was being completed, the paper [BLPR01] was electronically published. It contains two partial results in the direction of our work (see Remarks 3.10 and 3.19 for a discussion).…”
mentioning
confidence: 99%
“…If u ∈ Γ(X, W + ) is a nonvanishing section, then σ • u defines a non-degenerate, self-dual 2-form on X. It was shown in [BLPR00,Sco02] independently that if ∇ A u = 0 for some U (1)connection A, then σ • u defines a Kähler structure on X, compatible with a metric g ′ X = c • g X , c ∈ R. On the other hand, under mild conditions, it was shown that if u is a harmonic spinor, then σ • u defines a symplectic structure on X. Scorpan [Sco02] gave a charaterization of the Kähler and symplectic 2-forms that lie in the image of the quadratic map.…”
Section: Introductionmentioning
confidence: 96%